Comparative Expression Profiling of Snf2 Family Genes During Reproductive Development and Stress Responses in Rice - Guo, Mingliang; Zhao, Heming; He, Zhimei; Zhang, Wenchao; She, Zeyuan; Mohammadi, Mohammad Aqa; Shi, Chao; Yan, Maokai; Tian, Dagang; Qin, Yuan (Frontiers in Plant Science, 2022)
Snf2 protein family, as chromatin remodeling factors, is an enormous and most diverse protein family, and contributes to biological processes of replication, transcription, and DNA repair using the energy of ATP hydrolysis. The members of Snf2 family proteins have been well characterized in Arabidopsis, rice, and tomato. Although this family received significant attention, few genes were identified uniquely for their roles in mediating reproductive development and stress tolerance in rice. In the present study, we comprehensively analyzed the expression profiling of Snf2 genes during reproductive development and biotic/abiotic stresses. Our results showed that five proteins (OsCHR712/715/720/726/739) are mainly localized in the nucleus, while OsCHR715/739 are expressed in the cell membrane. There were abundant cis-acting elements in the putative promoter of Snf2 genes, including dehydration, MeJA, MYB binding site for drought, ABA-responsive, and stress-responsive element. Most of the genes were induced immediately after M.oryzae infection at 12 hours post-infection (hpi). About 55% of the total genes were up-regulated under salt and drought stresses within all the time, and 22-35% of total genes were up-regulated at 3h. It was noteworthy that the seven genes (OsCHR705, OsCHR706, OsCHR710, OsCHR714, OsCHR721, OsCHR726, OsCHR737) were up-regulated, and one gene (OsCHR712) was down-regulated under salt and drought stresses, respectively. The deficiency of OsCHR726 mutations displayed a hypersensitive phenotype under salt stress. These results will be significantly useful features for validation of the rice Snf2 genes and facilitate understanding the genetic engineering of crops with improved to biotic and abiotic stresses.